Turmeric and Cumin Instead of Stock Cubes: An Internet Survey of Spices and Culinary Herbs Used in Poland Compared with Historical Cookbooks and Herbals - Łukasz Łuczaj; Jarosław Dumanowski; Cecylia Marszałek; Fabio Parasecoli (Plants, 2023)
(Background) Culinary cultures undergo dramatic changes due to globalization; however, the shift in the use of culinary spices and herbs is little documented. We aimed to list seasoning products used in contemporary Polish cuisine and assess whether they have roots in historic recipes. (Methods) Via an online questionnaire distributed via social media, we gathered data from 916 respondents from all over Poland. (Results) Altogether 132 single-ingredient taxa of plant or fungi species were mentioned in the questionnaire. Capsicums, black pepper, turmeric, oregano, cinnamon, marjoram, ginger, basil, thyme, and bay leaf were the 10 most quoted seasonings throughout the year. While local herbs are likely to have been long used in local cooking, the most commonly used spices have been known in Poland since at least 17–18th c. However, a few Asian, mainly Indian spices have become mainstream in the last few years. In particular, these are turmeric, cumin, and fenugreek. The seasonings which decreased the most are various seasoning mixes and stock cubes, unpopular due to the large amount of monosodium glutamate and salt. (Conclusions) Polish cuisine is undergoing a strong process of globalization, and curry spices have become standard cooking ingredients.